Learning from Students: Reflections from personal magazines in basic design course - Gelmez, Koray; Bagli, Humanur (Design and Technology Education: An International Journal, 2015)
Reflective writing is an efficient way of getting feedback from students. Paper-based or web-based course evaluation questionnaires alone may lack of collecting specific and detailed information, especially for the fields like design education. This study focuses on reflections captured from students via two different media – personal magazine and online questionnaire – in 2012 Spring Semester conducted in Basic Design II in the Department of Industrial Product Design at Istanbul Technical University (ITU), Turkey. Throughout the semester, each student was encouraged to write a diary weekly and expected to submit a photocopied page of it to reflect freely their impressions about the course and their experiences, written or visual, or both. At the end of the semester, students were expected to submit their diaries in the form of personal magazines. This data is valuable to see the development of the student in terms of design awareness and perceptions about the course specifically. Moreover, a specific web-based questionnaire is prepared and delivered to students in order to see the general tendencies about the course. Based on these data, we explore how we can learn and benefit from students’ reflections for Basic Design course mechanism and design education.